The novelist from Berlin - Alexander, V. S. (Kensington Publishing Corp., 2023)
"1920s Germany: Though the world has changed in the wake of the Great War, it is still ruled by men. Even a woman as resourceful and intelligent as Niki Rittenhaus needs alliances in order to survive. Her marriage to Rickard L̃nger, a movie producer for Berlin's Passport Pictures, seems convenient for them both. When Rickard succumbs to increasing pressure from the Nazis to make propaganda movies, a horrified Niki turns away from her own film aspirations and instead, begins to write. Niki's first novel, The Berlin Woman, is published under a pseudonym to great success. But Niki knows she cannot stay anonymous for long. The Nazis are cementing their power over Germany--and over her husband. Though she succeeds in escaping Rickard, he directs Hitler's Brownshirts to do the unthinkable: kidnap their daughter. With her books blacklisted, her life in danger, and Europe descending into war, Niki travels to Amsterdam, joins the Dutch Resistance, and then returns to war-torn Berlin determined to claim freedom for herself and her child, and to write her own story at last." --